Makna Biaya di Balik Tradisi Mogama di Kecamatan Pinolosian Kabupaten Bolaang Mongondow Selatan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the meaning of costs behind the implementation of the Mogama tradition in the people of Pinolosian District, South Bolaang Mongondow Regency. The main problem is how economic aspects affect the meaning, implementation, and preservation of the Mogama tradition in the midst of the social dynamics of Pinolosian society. The Mogama tradition is a traditional wedding procession that has social, cultural, and spiritual values, but it has significant economic consequences.This study uses a qualitative method with an ethnographic approach through participatory observation, in-depth interviews, and documentation. The research informants consisted of traditional leaders, religious leaders, village governments, implementing families, and the general public. The results of the study showed that the total cost incurred in the Mogama procession in Nunuk Village in one family reached Rp16,250,000, which was divided into four main stages, namely deliberation, tampangkoi in gama (early pick-up), pinomama'an (eating betel nuts), and badati (shaking hands). The costs incurred are not only understood as financial expenditures, but also as a symbol of respect, a form of social investment, and a means of strengthening kinship ties and customary legitimacy. Thus, the meaning of cost in the Mogama tradition reflects the balance between the economic, social, and cultural dimensions that are the foundation of the sustainability of the Pinolosian tradition.